Rethinking visual journaling in the creative process: Exploring pedagogic implications - de Beer, C. (South African Journal of Higher Education, 2018)
I lecture jewellery design at a university of technology in South Africa. Through this study, I wish to arrive at a deeper understanding of my own creative process, so that I can facilitate the creative development of my students. The focus of this paper is the visual journal, or reflective sketchbook, which I require my students to keep. To establish the relationship between my creative practice and visual journaling, I analysed a creative poetic performance I delivered at the South African Educational Research Association’s (SAERA) 2016 conference. Using the little-c definition of creativity, I analyse the threads that constituted and contributed to my performance, to see how aspects of self-manifested within this creative process. I did the analysis by conducting an autoethnographic self-interview, and then examining the responses. To my surprise, I discovered that the inspiration for my own creative work does not necessarily originate in my visual journal and that the visual journal could play a more useful role, if used as a prompt for reflective conversations.